2015
DOI: 10.2174/156720501205150526115003
|View full text |Cite
|
Sign up to set email alerts
|

Functional Activities Questionnaire Items that Best Discriminate and Predict Progression from Clinically Normal to Mild Cognitive Impairment

Abstract: Background Impairment in instrumental activities of daily living (IADL) emerges in the transition from mild cognitive impairment (MCI) to Alzheimer’s disease (AD) dementia. Some IADL scales are sensitive to early deficits in MCI, but none have been validated for detecting subtle functional changes in clinically normal (CN) elderly at risk for AD. Methods Data from 624 subjects participating in the Alzheimer’s Disease Neuroimaging Initiative and 524 subjects participating in the Massachusetts Alzheimer’s Dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 46 publications
6
50
0
Order By: Relevance
“…Interestingly, these items were also the ones that most participants felt were more or much more difficult, suggesting that these items are more sensitive to functional impairment in this sample of participants with SCD and MCI. This is in line with research by Marshall et al (2015) who found that the item "assembling tax records" discriminated between healthy and MCI participants, and that lower scores on a "paying bills/balancing checkbook" item predicted progression from healthy to MCI. However, they also found that "heating water and turning off the stove" was sensitive to functional change, whereas in our sample most participants did not find a similar item "using the hob" more difficult.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Interestingly, these items were also the ones that most participants felt were more or much more difficult, suggesting that these items are more sensitive to functional impairment in this sample of participants with SCD and MCI. This is in line with research by Marshall et al (2015) who found that the item "assembling tax records" discriminated between healthy and MCI participants, and that lower scores on a "paying bills/balancing checkbook" item predicted progression from healthy to MCI. However, they also found that "heating water and turning off the stove" was sensitive to functional change, whereas in our sample most participants did not find a similar item "using the hob" more difficult.…”
Section: Discussionsupporting
confidence: 90%
“…The most recent criteria for mild cognitive impairment (MCI) due to Alzheimer's disease (AD) recognize the presence of subtle problems performing complex functional tasks; however the preservation of independence in functional abilities is a defining criteria (Albert et al, 2011). Nevertheless, difficulties performing IADL in MCI can be predictive of subsequent dementia (Di Carlo et al, 2016;Korolev et al, 2016;Marshall et al, 2015;Sikkes et al, 2011;Tabert et al, 2002). Assessment of subtle change in IADL could therefore provide vital information at the preclinical and prodromal stage of AD to support timely diagnosis and intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in a large-scale population study37 , FCSRT free recall in cognitively normal participants exhibited good sensitivity and fair specificity for AD prediction at 5 years (92% and 64% respectively), but showed poor positive predictive value (~8%). The observation that FAQ scores differed between future converters and controls supports recent evidence that impairment in certain instrumental activities of daily living predicts greater risk of progressing from a diagnosis of cognitively normal to MCI38 .Differences in GMD between subsequent converters and controls were limited to MTL, with the pattern of atrophy in EC showing left-sided predominance, as has been…”
supporting
confidence: 78%
“…This decline is typically measured by assessing activities of daily living (ADL), which can be divided into basic (e.g., self-maintenance skills) and instrumental functions (e.g., complex skills). To justify the diagnosis of PDD, ADL disabilities should be primarily caused by cognitive, not motor problems (Marshall et al, 2015). As PD is primarily a movement disorder, the distinction between motor and nonmotor contributions to ADL in PD is an obvious challenge (Cheon, Park, & Kim, 2015).…”
mentioning
confidence: 99%